Early leaf removal applied in warm climatic conditions: Impact on Tempranillo wine volatiles. (August 2017) - Moreno, Daniel; Valdés, Esperanza; Uriarte, David; Gamero, Esther; Talaverano, Inmaculada; Vilanova, Mar
Abstract: Defoliation is a cultural practice with demonstrated benefits in grape and wine quality. The objective of this study was to evaluate the effect of early leaf removal applied in warm climatic conditions on volatile composition of Tempranillo wines. During three consecutive vintages (2009–2011) wine volatile compounds (alcohols, C6 -compounds, ethyl esters, acetates, volatile acids, lactones and carbonyl compounds) from defoliated and non-defoliated vines were identified and quantified by GC–MS. Early leaf removal induced the increase of the concentration of all families of volatile compound quantified with exception of lactones. Significant increase was observed for 23 out 34 volatile compounds analyzed. The vintage effect also was shown, where the highest effect of defoliation was exhibited in 2009 vintage. Principal component analysis (PCA) showed a good separation of defoliation, non-defoliation and vintage according to wine volatile composition. The analysis of odour activity value (OAV) exhibited an increase of fruity and floral odour on Tempranillo wines when early defoliation was applied. Graphical abstract: Highlights: Early defoliation is a cultural practice with benefits in grape and wine quality. Early leaf removal increased the volatile concentration of Tempranillo wine. A significant increase was observed for 23 out 34 volatile compounds analyzed. Defoliation increased fruity and floral aroma on Tempranillo wines.